(untitled) (Research, Society and Development, 2023)
It stands out that pathological anxiety is a highly prevalent comorbidity in Brazil and that can cause personal damage to family and social life. In contemporary times, there is a need for the emergence of new therapies that help in the treatment of this pathology. With this, it is postulated that phytocannabinoids have peculiar actions in the nervous system, and exert important anxiolytic and neuroprotective effects. This research aims to gather data in the literature through a literature review to demonstrate the action of endocannabinoids in the treatment of anxiety disorders in order to elucidate their mechanism of action as well as their benefits in anxiety. For the present work, a bibliographic review was used, which took place through a search on the Web of science platforms, MEDLINE (PubMed) and LILACS, using the following descriptors: Cannabidiol, CBD and anxiety, which found 63 articles in the range of 10 years old. By means of an analytical and critical method, articles in Portuguese and English were selected that correlated the phytocannabinoid with pathological anxiety. It is concluded, therefore, that one of the main compounds of Cannabis Sativa, CBD, is capable of decreasing the activation of the amygdala and hippocampus. Therefore, this review demonstrated that cannabidiol has particular actions in the central nervous system, exerting potential anxiolytic and neuroprotective effects, modulating excitatory and inhibitory neurotransmission. Although the evidence is very encouraging, it is pointed out that doctors and potential users should consider the risk and benefit in the decision to use.